2022
DOI: 10.1590/0034-7167-2020-0545
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding and professionals from the family health strategy

Abstract: Objectives: to analyze the perception of health professionals about exclusive breastfeeding in Family Health Strategy units in the city of Macaé. Methods: qualitative study carried out in four units of the Family Health Strategy in the city of Macaé, Rio de Janeiro. Thirty health professionals were interviewed from March to May 2019. Textual contents were processed in the IRaMuTeQ® software by the Descending Hierarchical Classification. Results: professionals use different strategies for actions to promote, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…6,8,9,10 O importante papel dos profissionais de saúde no incentivo ao aleitamento materno exclusivo, desde o acompanhamento pré-natal até o pós-natal, reforça quanto seus conhecimentos sobre amamentação são relevantes. 35 Contudo, a pergunta relacionada ao significado do aleitamento materno predominante foi respondida de forma adequada apenas por dois dos participantes, reforçando as evidências de outro estudo desenvolvido com profissionais de saúde da ESF em Belo Horizonte (MG), tanto entre ACS quanto de outras áreas (enfermeiros, médicos generalistas e pediatras). 36 O conhecimento sobre os diferentes tipos de aleitamento materno é destacado pelo Ministério da Saúde do Brasil pela sua importância para a oferta de orientações corretas, revelando-se que ações educativas às mães com foco na administração de líquidos não nutritivos nos primeiros meses de vida da criança podem evitar efeitos nocivos à saúde infantil.…”
Section: Discussionunclassified
“…6,8,9,10 O importante papel dos profissionais de saúde no incentivo ao aleitamento materno exclusivo, desde o acompanhamento pré-natal até o pós-natal, reforça quanto seus conhecimentos sobre amamentação são relevantes. 35 Contudo, a pergunta relacionada ao significado do aleitamento materno predominante foi respondida de forma adequada apenas por dois dos participantes, reforçando as evidências de outro estudo desenvolvido com profissionais de saúde da ESF em Belo Horizonte (MG), tanto entre ACS quanto de outras áreas (enfermeiros, médicos generalistas e pediatras). 36 O conhecimento sobre os diferentes tipos de aleitamento materno é destacado pelo Ministério da Saúde do Brasil pela sua importância para a oferta de orientações corretas, revelando-se que ações educativas às mães com foco na administração de líquidos não nutritivos nos primeiros meses de vida da criança podem evitar efeitos nocivos à saúde infantil.…”
Section: Discussionunclassified
“…Low adherence to exclusive breastfeeding (EBF) is a global phenomenon, as reported by the United Nations Children's Fund (UNICEF) and the World Health Organization (WHO), which have shown that only 23 out of 194 countries achieve exclusive breastfeeding rates above 60%. Exclusive breastfeeding rates in Brazil have improved in recent decades; however, the prevalence of 45.8% is still below the WHO recommendations for 2030 (1)(2)(3) . Often, women remain silent about their difficulties because they bear the burden of early weaning and its consequences for their child's health alone.…”
Section: Introductionmentioning
confidence: 99%